Spore subscribers pass the 50,000 mark - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Over 50,000 institutions and individuals now receive subscriptions to the English and French editions of Spore and to theirsister publication in the Portuguese language, Esporo. Spore is sent to people living in ACP countries who ask for a...